Syntheses, structures, anomalous phase transition and optical properties of two new polymorphic α- and β-LiMoPO6. Issue 44 (28th October 2019) - Liu, Haonan; Wu, Hongping; Yu, Hongwei; Hu, Zhanggui; Wu, Yicheng
Abstract : Two new polymorphic α- and β-LiMoPO6 were synthesized, and they exhibit anomalous phase transition caused by the stretching of the [MoO3 O3 PO]∞ chain. Abstract : New polymorphous phases, α- and β-LiMoPO6, have been successfully synthesized by the high temperature solution technique and their structures have been determined by single crystal X-ray diffraction. α-LiMoPO6 crystallizes in the orthorhombic space group Pbcn (No. 60) with a = 12.1141(4) Å, b = 8.9251(3) Å and c = 8.7389(3) Å, while β-LiMoPO6 crystallizes in the monoclinic space group P 21 / c (No. 14) with a = 6.3441(3) Å, b = 7.5949(3) Å, c = 9.3430(4) Å and β = 94.546(4)°. Both structures exhibit a similar three-dimensional (3D) framework composed of MoO6 octahedra and PO4 tetrahedra. Interestingly, an anomalous phase transition, i.e. the high-temperature β-LiMoPO6 phase exhibiting larger density than the low-temperature α-LiMoPO6, has been observed. Detailed structural analyses show that the anomalous phase transition mainly originates from the 'straightened' effect of the zigzag [MoO3 O3 PO]∞ chains in their structures. Furthermore, the optical and thermal properties of two compounds are also reported.